Tracing the range shifts of African tree ferns: Insights from the last glacial maximum and beyond - Mwihaki J. Karichu; Boniface K. Ngarega; Joyce M. Jefwa; Bette A. Loiselle; Emily B. Sessa (Ecological Informatics, 2024)
African tropical forests are experiencing rapid decline as a result of several factors, including increasing population pressure, recurrent wildfires, selective logging practices, land use changes, intensified agricultural activities, and other social and economic issues. Using MaxEnt, paleoclimatic data, and future climate scenarios, the present study seeks to explore the presence of tree ferns in tropical and Saharan Africa during the Last Glacial Maximum, African Holocene Humid Period (AHHP; ca. 14,500–5000 years ago) and to project the effects of climate change on the distribution of tree ferns in Africa under two future climatic scenarios, Representation Concentration Pathways (RCP) 4.5 and 8.5. Our study reveals that despite a significant increase in precipitation during the AHHP, precipitation distribution was variable and insufficient to support the five tree fern species examined in this study. While some tree fern species have experienced range shifts over time, we found that most of them have maintained their presence within refuge areas that probably endured the late Pleistocene extinction event. These refugia provided a haven for some tree ferns, allowing them to persist and survive amidst challenging and varying environmental conditions. This highlights tree ferns' remarkable adaptability in changing climate as well as the critical importance of these refugial areas in safeguarding their populations during climatic upheaval. Our study further demonstrates that different species respond to climate change differently, with some experiencing minimal range contractions of 2.0 %, up to more than 57.0 % range expansion in other species. Preserving refugia not only safeguards tree fern populations but also contributes to conserving overall forest biodiversity and ecosystem functioning. This knowledge is crucial for implementing targeted conservation actions that promote sustainable forest management and can mitigate the threats posed by climate change and anthropogenic activities in African closed wet forests.